Is Rising Household Debt Affecting Retirement Decisions? - Barbara A. Butrica; Nadia S Karamcheva (Institute of Labor Economics (IZA), 2020)
Household debt among older Americans approaching retirement has increased dramatically over the past couple of decades. Older households have become increasingly more indebted and more leveraged. While mortgages remain the predominant type of debt among households in their 50s and 60s, in recent years, student loan debt has also risen among these households. Using household survey data to examine how late life debt affects retirement decisions, we find that more indebted older adults are more likely to work, less likely to be retired, and on average expect to work longer than those with less debt.
Keywords: J21; J26; 330; older adults; household debt; mortgages; student loan debt; retirement; social security